1981
DOI: 10.1111/j.1524-4725.1981.tb00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal‐Cell Carcinoma of the Vulva

Abstract: Basal‐cell carcinoma is an uncommon neoplasm on the vulva and is indistinctive in appearance there. A review of the literature shows that basal‐cell carcinomas on the vulva are insidious in development, that they are not recognized early, and that wide surgical excision is the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…This incidence is higher than the expected 2-3% reported in most previous studies [1,[3][4][5][6][8][9][10]12,13]. Nevertheless, some studies have shown that the relative frequency ranges from 0.8 to 14.7% [2,7,11].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…This incidence is higher than the expected 2-3% reported in most previous studies [1,[3][4][5][6][8][9][10]12,13]. Nevertheless, some studies have shown that the relative frequency ranges from 0.8 to 14.7% [2,7,11].…”
Section: Discussioncontrasting
confidence: 71%
“…Most distressing are the data concerning patient delay in seeking medical help [6,7,8,13]. This attitude of the patients is, most probably, due to false modesty and fear.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of disease prior to diagnosis is often protracted, with the patient seeking medical advice years after first noticing the lesion. There may be subsequent delay because of the innocuous appearance of such lesions 14 …”
Section: Commentsmentioning
confidence: 99%
“…Also, physicians might initially mistake these cancers for either inflammatory or infectious disease2,23. It is recommended that physicians must consider the skin cancer as a one of the differential diagnosis and biopsy of all suspect lesions should be performed, even if the BCC at these regions can sometimes seem innocuous.…”
Section: Discussionmentioning
confidence: 99%